Henrikas Jasiūnas – the founder of the museum of Lithuanian mathematicians - Laurinčikas, Antanas; Verikaitė, Vitolda (Lietuvos matematikos rinkinys, 2016)
In the paper, a survey on the life and activity of the former and longtime chief of the Lithuanian museum of mathematicians Doc. Henrikas Jasiūnas (1925–2015) is given. The main directions of the museum work in variuos periods are shortly discussed, the public importance of this cultural institution is disclosed.
Keywords: pedagogical; organizing; cultural and public education work; photos; private collections of mathematicians; scientific works; textbook